Disparities in quality of cancer care: The role of health insurance and population demographics. Issue 50 (December 2017) - Parikh-Patel, Arti; Morris, Cyllene R.; Kizer, Kenneth W.
Abstract : Abstract: Escalating costs and concerns about quality of cancer care have increased calls for quality measurement and performance accountability for providers and health plans. The purpose of the present cross-sectional study was to assess variability in the quality of cancer care by health insurance type in California. Persons with breast, ovary, endometrium, cervix, colon, lung, or gastric cancer during the period 2004 to 2014 were identified in the California Cancer Registry. Individuals were stratified into 5 health insurance categories: private insurance, Medicare, Medicaid, dual Medicare and Medicaid eligible, and uninsured. Quality of care was evaluated using Commission on Cancer quality measures. Logistic regression models were generated to assess the independent effect of health insurance type on stage at diagnosis, quality of care and survival after adjusting for age, sex, race/ethnicity, and socioeconomic status (SES). A total of 763, 884 cancer cases were evaluated. Individuals with Medicaid or Medicare-Medicaid dual-eligible coverage and the uninsured had significantly lower odds of receiving recommended radiation and/or chemotherapy after diagnosis or surgery for breast, endometrial, and colon cancer, relative to those with private insurance. Dual eligible patients with gastric cancer had 21% lower odds of having the recommended number of lymph nodes removed and examined compared to privately insured patients. After adjusting for known demographic confounders, substantial and consistent disparities in quality of cancer care exist according to type of health insurance in California. Further study is needed to identify particular factors and mechanisms underlying the identified treatment disparities across sources of health insurance.